Model of knowledge management: comprehensive view - Bernal Torres, César A (Cuadernos de Administración, 2011)
This article seeks to design a comprehensive model of the management or administration of knowledge as a strategic resource to enhance the competitive capacity of organizations. The purpose of the model is to contribute to responding to two basic questions from many company directors and researchers on the topic within the scope of developing nations: a) the need for local management models pertinent to the reality of the organizations, and b) the integration of the diversity of dispersed models existing in this field to facilitate their understanding and application. The construction of the model was carried out from a broad bibliographic review on the topic, field work within the reference context with interviews of company directors, and an analysis by experts.